Experimental Investigation on Thermal Management of Electric Vehicle Battery Module with Paraffin/Expanded Graphite Composite Phase Change Material - Jiangyun Zhang; Xinxi Li; Fengqi He; Jieshan He; Zhaoda Zhong; Guoqing Zhang (International Journal of Photoenergy)
The temperature has to be controlled adequately to maintain the electric vehicles (EVs) within a safety range. Using paraffin as the heat dissipation source to control the temperature rise is developed. And the expanded graphite (EG) is applied to improve the thermal conductivity. In this study, the paraffin and EG composite phase change material (PCM) was prepared and characterized. And then, the composite PCM have been applied in the 42110 LiFePO4 battery module (48 V/10 Ah) for experimental research. Different discharge rate and pulse experiments were carried out at various working conditions, including room temperature (25°C), high temperature (35°C), and low temperature (−20°C). Furthermore, in order to obtain the practical loading test data, a battery pack with the similar specifications by 2S∗2P with PCM-based modules were installed in the EVs for various practical road experiments including the flat ground, 5°, 10°, and 20° slope. Testing results indicated that the PCM cooling system can control the peak temperature under 42°C and balance the maximum temperature difference within 5°C. Even in extreme high-discharge pulse current process, peak temperature can be controlled within 50°C. The aforementioned results exhibit that PCM cooling in battery thermal management has promising advantages over traditional air cooling.